Genetic substructure of Guizhou Tai-Kadai-speaking people inferred from genome-wide single nucleotide polymorphisms data - Ren, Zheng; Yang, Meiqing; Jin, Xiaoye; Wang, Qiyan; Liu, Yubo; Zhang, Hongling; Ji, Jingyan; Wang, Chuan-Chao; Huang, Jiang (Frontiers in Ecology and Evolution, 2022)
The genome-wide characteristics and admixture history of the Tai-Kadai-speaking populations are essential for understanding the population genetic diversity in southern China. We genotyped about 700,000 single nucleotide polymorphisms (SNPs) of 239 individuals from six Tai-Kadai-speaking populations residing in the mountainous Guizhou Province of southwestern China. We merged the genome-wide data with available populations and ancients in East and Southeast Asia to infer Tai-Kadai-speaking populations' admixture history and genetic structure. We observed a genetic substructure within the studied six populations in the PCA, ADMIXTURE, ChromoPainter, GLOBETROTTER, f-statistics, and qpWave analysis. The Dong, Zhuang, and Bouyei people had a strong genetic affinity with other Tai-Kadai-speaking and Austronesian groups in the surrounding area. However, Gelao showed an affinity to Sino-Tibetan groups, and Mulao people were genetically close to Hmong-Mien populations. qpAdm further illuminated that Gelao and Dong_Tongren composited more Han-related ancestry than Dong, Zhuang, Bouyei and Mulao people. Meanwhile, we observed high frequencies of Y-chromosome haplogroup O in studied Tai-Kadai-speaking groups except for Gelao people with a high haplogroup N frequency. From the maternal side, haplogroup M7 was frequent in studied populations except for Tongren Dong, who had a high frequency of haplogroup B5. Our newly reported data are helpful for further exploring population dynamics in southern China.